The assessment of take-off symmetry in ski jumping - Janura, M.; Elfmark, M.; Svec, P. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Wearing jumping boots during take-off Simulation reduces speed and increases duration of the take-off phase (Schwameder et al., 1997). A diverse footwear is reflected in take-off kinematics and in the engagement of muscles (Virmavirta & Komi, 2000; Virmavirta & Komi, 2001). "Natural" variability and asymmetry (in the "physiological" extent) is a component of healthy biological Systems, however the sequence of movements beyond the ski jumping hill edge requires reduction in such an asymmetry. This study aims to compare ' the magnitudes of take-off forces on the right and left lower limbs during the take-off.